Extracting the chiral anomaly from e + e − → 3π - Martin Hoferichter; Bai-Long Hoid; Bastian Kubis (Journal of High Energy Physics)
Abstract The strength of the interaction of three pions and a photon, F 3π is predicted by the axial anomaly in terms of the pion decay constant, a relation that is frequently used to constrain low-energy radiative processes involving pions, but only tested experimentally at the 10% level. Here, we present a new avenue to test this prediction, via a fit of a dispersive description of the γ ∗ → 3π amplitude to data for e + e − → 3π. From the global fit to SND, CMD-2, and BaBar data we obtain F 3π = 33.1(1.7) GeV−3, in agreement with the chiral prediction at the level of 5%. We also consider dispersive fits to the recent data by Belle II, in which case we observe tensions with the dispersive constraints, the width parameters of ω and ϕ, and the chiral anomaly.